The Paper on The Matrix Valued Time Series - Gençoğlu, M.tuncay (My University, 1997)
In this paper random series oscillatory were exemine in matrix valued time series.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Matrix Time series